Evaluation of the Pig-a, micronucleus, and comet assay endpoints in a 28-day study with ethyl methanesulfonate - Gunther, William C.; Coffing, Stephanie L.; Dickinson, Donna A.; Engel, Maria E.; Fiedler, Ronald D.; O'Lone, Susan D.; Sanok, Kelley E.; Thiffeault, Catherine J.; Shutsky, Thomas J.; Schuler, Maik J.; Dobo, Krista L. (Environmental and molecular mutagenesis, 2014)
Ethyl methanesulfonate (EMS) was evaluated as part of the validation effort for the rat Pig‐a mutation assay and compared with other well‐established in vivo genotoxicity endpoints. Male Sprague‐Dawley (SD) rats were given a daily dose of 0, 6.25, 12.5, 25, 50, or 100 mg/kg/day EMS for 28 days, and evaluated for a variety of genotoxicity endpoints in peripheral blood, liver, and colon. Blood was sampled pre‐dose (Day 1) and at various time points up to Day 105. Pig‐a mutant frequencies were determined in total red blood cells (RBCs) and reticulocytes (RETs) as RBCCD59− and RETCD59− frequencies. The first statistically significant increases in mutant frequencies were seen in RETs on Day 15 and in RBCs on Day 29 with the maximum RETCD59− on Day 29 and of RBCCD59− on Day 55. The lowest dose producing a statistically significant increase of RETCD59− was 12.5 mg/kg on Day 55 and 25 mg/kg for RBCCD59− on Day 55. EMS also induced significant increases in % micronucleated RETs (MN‐RETs) in peripheral blood on Days 3, 15, and 28. No statistically significant increases in micronuclei were seen in liver or colon. Results from the in vivo Comet assay on Day 29 showed generally weak increases in DNA damage in all tissues evaluated with little evidence for accumulation of damage seen over time. The results with EMS indicate that the assessment of RBCCD59− and/or RETCD59− in the Pig‐a assay could be a useful and sensitive endpoint for a repeat dose protocol and complements other genotoxicity endpoints. Environ. Mol. Mutagen. 55:492–499, 2014. © 2014 Wiley Periodicals, Inc.